ANALISIS HUKUM ATAS TANGGUNG JAWAB NOTARIS TERHADAP TERJADINYA PERBEDAAN SAKSI DALAM SALINAN AKTA DENGAN MINUTA AKTA (STUDI KASUS PUTUSAN M.A NO. 2468-K/PID/2006) - Pangeran Batara Bonardo munte (jurnal.unprimdn.ac.id, 2022)
The result of the research shows that the evidence inhered to the authentic deed is tangible evidence, formal evidence, or material evidence. In this case, the Panel of Judges of the Supreme Court use material evidence, the truth of the content of authentic deed, because in their legal opinion, in this casse, the problem is the content of the deed not the names of the witnesses. The Notary has issued the copy of the deed with different witnesses from those that are specified in the deed minute which later becomes a claim or complaint from the person who has complaint about the deed made by the Notary. Therefore, the Notary can be sued and is required to take the responsibility in the criminal law (if the criminal count is fulfilled), civil law (if Article 1365 of the Civil Code is fulfilled), state administratuve law and law No. 2/2014 (if Article 16 paragraph 1. Letter d of law No. 12/2014 on Notarial Position is fulfilled). The Judge of the Supreme Court hands down the Ruling No. 2468 K/Pid/2006 which states that the Court rejects the cassation appeal of the appelant, the prosecuting attorney or public prosecutor in the District Attorney’s Office or the Provincial General Attorney’s Office of Surabaya because the judge has his opinion that the case of witnesses in the Notarial Deed is nit the case material.Keyword : Notary, Deed Minute, Deed Copy, Liability